2021
DOI: 10.1248/bpb.b21-00381
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Ameliorates Cognitive Impairment and Neuroinflammation in an Oligomeric Aβ Induced Alzheimer’s Disease Mouse Model <i>via</i> Inhibition of Microglial Activation and NADPH Oxidase Expression

Abstract: Microglial activation and neuroinflammation induced by amyloid β (Aβ) play pivotal roles in Alzheimer's disease (AD) pathogenesis. Astragaloside IV (AS-IV) is one of the major active compounds of the traditional Chinese medicine Astmgali Radix. It has been reported that AS-IV could protect against Aβ-induced neuroinflammation and cognitive impairment, but the underlying mechanisms need to be further clarified. In this study, the therapeutic effects of AS-IV were investigated in an oligomeric Aβ (oAβ) induced A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Multiple studies have demonstrated that excessive oxidative stress accompanied by impaired antioxidant capacity in T2DM encouraged the generation of ROS that further led to neuronal damage and cognitive dysfunction in T2DM (Valko et al, 2007 ; Gocmez et al, 2019 ; Michailidis et al, 2022 ). Furthermore, studies have shown that AS-IV exerts neuroprotective effects on AD and chronic cerebral hypoperfusion-induced dementia depending on the inhibition of oxidation stress (Kim et al, 2015 ; Chen et al, 2021 ). Consistent with the preceding studies, our current study showed that the activities of SOD were decreased, while the MDA levels were increased in T2DM mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated that excessive oxidative stress accompanied by impaired antioxidant capacity in T2DM encouraged the generation of ROS that further led to neuronal damage and cognitive dysfunction in T2DM (Valko et al, 2007 ; Gocmez et al, 2019 ; Michailidis et al, 2022 ). Furthermore, studies have shown that AS-IV exerts neuroprotective effects on AD and chronic cerebral hypoperfusion-induced dementia depending on the inhibition of oxidation stress (Kim et al, 2015 ; Chen et al, 2021 ). Consistent with the preceding studies, our current study showed that the activities of SOD were decreased, while the MDA levels were increased in T2DM mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AS-IV has been proven to exert potent protective effects on diabetic nephropathy via inhibiting the expressions of inflammatory genes in a rat model of T2DM (Gui et al, 2013a ). Meanwhile, a previous study indicated that AS-IV was an effective anti-inflammatory agent in the treatment of an AD mouse model (Chen et al, 2021 ). In our study, the levels of TNF-α, IL-6, and IL-1β were increased in T2DM mice, while treatment with AS-IV exhibited a significantly anti-inflammatory prowess by decreasing the levels of those pro-inflammatory cytokines in T2DM mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Astragaloside IV promotes mitochondrial autophagy, thus reducing the accumulation of damaged mitochondria and the production of mitochondrial reactive oxygen species. 14,[96][97][98][99][100][101][102][103] To conclude, the mechanism of Astragali Radix against aging-related neurodegenerative diseases mainly involves anti-neurotoxicity, anti-neuroinflammation and antioxidation. Astragali Radix is a dietary herb, applied with many potential signal regulations, including neurotransmitters and receptors, anti-inflammatory activity, inhibiting amyloid aggregation, inducing myelin repair and neurogenesis, and activating signal pathways related to neurological diseases.…”
Section: Astragali Radixmentioning
confidence: 98%
“… Chen et al (2021) used AβO-infused mice to explore the anti-neuroinflammation activity of AS-IV. They found that injection of AβO significantly upregulated expression of ROS, IL-1β, IL-6, and TNF-α, which are biomarkers of inflammation.…”
Section: Potential Mechanisms Underlying the Therapeutic Effect Of Bi...mentioning
confidence: 99%